Microscopic evaluation and Descriptive study of Crystals and Uroliths encountered in the Urinary tract system of Cats and Dogs - Polat, Eren; Kaya, Emre; Oral, Münir Mert; Çelikdemir, Nisanur (Universidad del Zulia, Facultad de Ciencias Veterinarias, 2022)
In this study, the presence and types of urine crystals in cats and dogs with urolithiasis/crystaluria and the effects of some demographic factors (such as type, breed, age, sex, sterilization status) on them were evaluated. In the study, physical, chemical and sediment examinations of urine samples of 67 cats and dogs were performed. It was determined that 83.58% of the animals with crystals in their urine were male. It was determined that 63.64% of the female animals and 44.64% of the male animals with crystals detected in the urinary tract were sterilized. It was determined that urinary crystals were more common in cats between 1-3 years of age (AO) and in dogs older than 3 AO. It was determined that calcium oxalate crystal (64.41%) in cats and struvite crystal (50%) in dogs were the most common crystals. It was determined that urine crystals were found mostly in cross breeds in cats and dogs. It was determined that most of the cats and dogs with urine crystals were fed with home meals and non-branded foods. It was determined that urinary tract infections had an effect on the formation of urine crystals. As a result, it was concluded that it is important in terms of Veterinary Medicine that such studies should be routinely performed, especially in the United States of North America (such as the Minnesota Urolith Center), since urine crystals cause significant lower urinary system diseases. © (2022). All Rights Reserved.
Evaluación microscópica y estudio descriptivo de cristales y urolitos encontrados en el sistema de vías urinarias de perros y gatos
Keywords: Calcium oxalate; cat; dog; struvite; urolite